Examining the role of knowledge and trust on vaccine confidence in North Dakota among university students, faculty, and staff - Mary Bruns; Tanis Walch; Claire Wagner; Rylee Bergeron; Soojung Kim (BMC, 2024)
Abstract Background Vaccination is one of the greatest tools for individuals to stay healthy. Individuals are, however, often exposed to misinformation via digital and social media, and thus, may miss the opportunity to develop scientific knowledge about vaccines and trust in relevant stakeholders. This has a damaging impact on vaccine confidence. Understanding vaccine confidence is particularly important in North Dakota, where vaccination rates are lower than national averages. Objectives The objectives of this research are to examine the association between vaccine confidence and three potential sources of it, namely, trust, vaccine knowledge, and vaccine information sources and to investigate the relative strength of three vaccine confidence sources, while accounting for covariates. Methods Students (n = 517, 56.6%) and staff and faculty (n = 397, 43.4%) at the University of North Dakota (n = 914) completed an online survey. Logistic regressions estimated odds ratios (OR) and 95% confidence intervals (CI) for associations among trust in doctors, family/friends, government health agencies, charitable organizations, and religious organizations, vaccine knowledge, vaccine information sources as well as vaccine confidence, accounting for gender, race, marital status, age, religion, political ideology, education, and health status. Results The mean age of participants was 29.43 years (SD = 13.48). Most were females (71.6%) and white (91.5%). Great trust in doctors (OR = 3.29, p < 0.001, 95%CI 1.89, 5.73) government health agencies (OR = 2.95, p < 0.001, 95%CI 2.13, 4.08) and vaccine knowledge (OR = 1.28, p < 0.001, 95%CI 1.18, 1.38) had higher odds of vaccine confidence. Using Internet Government source as the primary source of vaccine information (OR = 1.73, p < 0.05, 95%CI 1.22, 2.44) showed higher odds of vaccine confidence before all independent variables were introduced, but it became non-significant after they were introduced. Trust in government health agencies showed strongest associations with vaccine confidence. Conclusion Multiple stakeholders are necessary to ensure verified, accessible, and accurate information in order to advance vaccine confidence in rural, conservative areas.